INTERNAL CONTROL SYSTEM AND ORGANIZATIONAL COMMITMENT TO REGIONAL GOVERNMENT MANAGERIAL PERFORMANCE - Nur Azizah Basmar; Muhammad Zulfikar Rosihan (Contemporary Journal on Business and Accounting, 2022)
Purpose – This study aims to determine whether the Internal Control System, and Organizational Commitment affect the performance of the Regional Government Managerial in GOWA district SKPD Design/methodology/approach – The method of data analysis uses multiple linear regression techniques Findings – The results of this study indicate that the influence of the Internal Control System, and Organizational Commitment has an influence on the Managerial Performance of Local Governments. Based on the results of the R square test in this study is relatively strong. This is because almost all respondents answered strongly agree and agree. Originality – Collecting data using primary data obtained from 51 respondents in GOWA district SKPD